Hubungan Gaya Belajar dengan Hasil Belajar PKK I Mahasiswa DIII Kebidanan Tingkat II Stikes Eka Harap Palangka Raya: Relation Between Learning Style with Student Learning Outcomes PKK I DIII Midwifery Level II in STIKES Eka Harap Palangka Raya - Ivana Devitasari; Stefanicia Stefanicia (Jurnal Surya Medika (JSM), 2022)
Introduction: Learning outcomes are evidence of the success of the students undergoing a learning process and proof of success for educators in educating students to master the things they are taught by the standards of competence. Correspondence between learning styles and learning outcomes would affect one's success in learning. Objectives: The type and design of research using correlational analytic research with cross sectional approach, namely, a study on some populations, were observed simultaneously. The study population was all active students in PBM, namely class A and B, as many as 101 people. The sampling technique used was simple random sampling obtained amounted to 50 students. Collecting data using a closed questionnaire containing questions about the style of learning and learning outcomes for the PKK I observations. The data in the form of univariate analysis technique to describe the frequency distribution table and bivariate analysis techniques Spearman rank test with α = 0,05. Results: Results showed that there was a significant relationship between learning styles with learning outcomes PKK I, with p = 0,049 (α = 0,05). Conclusion: It can be concluded that the kinesthetic learning style will stimulate psychomotor DIII Midwifery students in obtaining the study results on the optimal PKK I in STIKES Eka Harap Palangkaraya.